2003
DOI: 10.1890/02-0370
|View full text |Cite
|
Sign up to set email alerts
|

Might Nitrogen Limitation Promote Omnivory Among Carnivorous Arthropods?

Abstract: Omnivory is a frequent feeding strategy in terrestrial arthropods, occurring across a diversity of taxa occupying a wide array of habitats. Because omnivory has important consequences for broad areas of theoretical and applied ecology, it is essential to understand those factors that favor its occurrence. Here we address the limiting role of nitrogen in promoting omnivory, not so much from the historical perspective of herbivores supplementing their nutrient-poor plant diet, but by extending the argument to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
271
5
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(285 citation statements)
references
References 77 publications
(165 reference statements)
5
271
5
4
Order By: Relevance
“…In contrast, even when orb and sheet‐tangle web spiders showed significant elemental imbalances with their prey, these elemental mismatches were lower than those evidenced for tangle web spiders, except for C:N (and N) content. Overall, these results suggest that generalist spiders, such as orb and sheet‐tangle species, could overcome elemental imbalances by having a more varied diet than prey specialists (Denno & Fagan, 2003). …”
Section: Discussionmentioning
confidence: 94%
“…In contrast, even when orb and sheet‐tangle web spiders showed significant elemental imbalances with their prey, these elemental mismatches were lower than those evidenced for tangle web spiders, except for C:N (and N) content. Overall, these results suggest that generalist spiders, such as orb and sheet‐tangle species, could overcome elemental imbalances by having a more varied diet than prey specialists (Denno & Fagan, 2003). …”
Section: Discussionmentioning
confidence: 94%
“…This predicted pattern is supported by data on invertebrates showing that the percentage of body nitrogen increases as trophic levels are ascended, whereas the ratio of carbon to nitrogen (C : N) in food versus the body of consumers (C : N food/C : N consumer) narrows progressively (Denno and Fagan 2003). Denno and Fagan (Denno and Fagan 2003;Fagan and Denno 2004) concluded from these trends in body elemental composition that carnivorous arthropods are nitrogen (protein) limited. This, they suggested, explains the tendency for many predators to demonstrate trophic omnivory -to feed not only on herbivores, but also on other carnivores (which, as we have seen, tend to have higher nitrogen concentration).…”
Section: The Nutritional Geometry Of Food Websmentioning
confidence: 85%
“…Several recent studies, however, suggest that the nutritional quality of food can influence a variety of behaviors in arthropods, including courtship (Wagner and Hoback, 1999;Holzer et al, 2003;Hunt et al, 2004;Bertram et al, 2006) and mating (Mallard & Barnard, 2004). In addition, it has been suggested that predatory arthropods such as spiders are frequently nutrient limited in nature (Denno and Fagan, 2003;Fagan and Denno, 2004) and that food quantity is also often limited (Wise, 1993;Wise, 2006). These studies in combination with our results suggest that under natural conditions, food quantity and/or quality could significantly affect female mate choice and the evolution of male secondary sexual traits.…”
Section: Discussionmentioning
confidence: 99%